2021
DOI: 10.1121/10.0005733
|View full text |Cite
|
Sign up to set email alerts
|

Toward inclusion of atmospheric effects in the aircraft community noise predictions

Abstract: This paper presents an atmospheric propagation model, based on ray acoustics, that accounts for realistic weather conditions in the evaluation of the noise footprint of an aircraft. Noise sources, obtained using the Ffowcs Williams and Hawkings acoustic analogy applied to scale-resolved flow simulation data, are stored on a hemisphere surrounding the vehicle. These noise sources are propagated using a propagation model that takes into account the vertical variability of air temperature and wind velocity. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Corresponding variations of the propagation conditions have for example been studied by Plotkin et al (2002), who ran aircraft noise simulations on an hourly basis with specific flight operations and weather conditions and compared resulting noise contours. Fuerkaiti et al (2021) reported "that weather conditions in the acoustic wave propagation can contribute to mismatch up to 4 dB(A) in the illuminated zone and a significant drop in the refractive shadow zone caused by the vertical air temperature and wind velocity gradients." The authors recommended the use of raytracing algorithms in aircraft community noise prediction to reproduce realistic atmospheric effects.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding variations of the propagation conditions have for example been studied by Plotkin et al (2002), who ran aircraft noise simulations on an hourly basis with specific flight operations and weather conditions and compared resulting noise contours. Fuerkaiti et al (2021) reported "that weather conditions in the acoustic wave propagation can contribute to mismatch up to 4 dB(A) in the illuminated zone and a significant drop in the refractive shadow zone caused by the vertical air temperature and wind velocity gradients." The authors recommended the use of raytracing algorithms in aircraft community noise prediction to reproduce realistic atmospheric effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fuerkaiti et al [15] developed a two-point 3D eigenray tracer that accounts for sound refraction due to vertical variability of air temperature and wind velocity gradients. Noise footprints of a UAM vehicle cruising at 2 km altitude over a flat ground under di erent weather conditions were evaluated.…”
Section: Insonification Edge Di↵ractionmentioning
confidence: 99%
“…In UYGUR, each Gaussian beam has the same initial amplitude and phase. Inclusion of complex source directivity into the acoustic footprint follows similar steps as described in [15]. In this work, those steps are adapted for the GBT procedures and briefly explained in the following.…”
Section: B Inclusion Of Complex Source Directivity Into the Acoustic ...mentioning
confidence: 99%
See 2 more Smart Citations